Ancestral function of the phytochelatin synthase C-terminal domain in inhibition of heavy metal-mediated enzyme overactivation. (16th September 2020) - Li, Mingai; Barbaro, Enrico; Bellini, Erika; Saba, Alessandro; Sanità di Toppi, Luigi; Varotto, Claudio
Abstract : The characterization of Marchantia polymorpha phytochelatin synthase provides novel insights into the evolutionary function of the enzyme's elusive C-terminus as a regulatory domain inhibiting enzyme overactivation by metal ions. Abstract: Phytochelatin synthases (PCSs) play essential roles in detoxification of a broad range of heavy metals in plants and other organisms. Until now, however, no PCS gene from liverworts, the earliest branch of land plants and possibly the first one to acquire a PCS with a C-terminal domain, has been characterized. In this study, we isolated and functionally characterized the first PCS gene from a liverwort, Marchantia polymorpha ( MpPCS ). MpPCS is constitutively expressed in all organs examined, with stronger expression in thallus midrib. The gene expression is repressed by Cd 2+ and Zn 2+ . The ability of MpPCS to increase heavy metal resistance in yeast and to complement cad1-3 (the null mutant of the Arabidopsis ortholog AtPCS1 ) proves its function as the only PCS from M. polymorpha . Site-directed mutagenesis of the most conserved cysteines of the C-terminus of the enzyme further uncovered that two twin-cysteine motifs repress, to different extents, enzyme activation by heavy metal exposure. These results highlight an ancestral function of the PCS elusive C-terminus as a regulatory domain inhibiting enzyme overactivation by essential and non-essential heavy metals. The latter finding may be relevant for obtaining crops with decreased root to shoot mobility of cadmium, thus preventing its accumulation in the food chain.